1997
DOI: 10.1021/ja963944q
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Utility of a New Soluble Copper Catalyst [CuBr−LiSPh−LiBr−THF]:  A Comparison with Other Copper Catalysts in Their Ability to Couple One Equivalent of a Grignard Reagent with an Alkyl Sulfonate

Abstract: A mixture of equal amounts of CuBr−SMe2, LiBr, and LiSPh in THF at 0 °C furnished a new soluble copper catalyst that was highly efficient at coupling primary, secondary, tertiary, aryl, vinyl, and allylic Grignard reagents to primary tosylates and primary Grignard reagents to secondary tosylates and mesylates, all with the use of only 1 equiv of Grignard reagent. The new catalyst was shown to be much more reactive than copper catalysts CuBr and Li2CuCl4 and more efficient in the transference of secondary and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
45
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…[2] This requirement causes serious waste of the precious organometallic species, in particular in the case of cuprate reagents (R 2 CuLi), which contain two transferable R groups. [3] To solve this problem, several research groups have developed copper-catalyzed alkylation reactions of Grignard reagents. [3][4][5] It was found that these catalytic reactions are much easier to carry out and considerably less expensive.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[2] This requirement causes serious waste of the precious organometallic species, in particular in the case of cuprate reagents (R 2 CuLi), which contain two transferable R groups. [3] To solve this problem, several research groups have developed copper-catalyzed alkylation reactions of Grignard reagents. [3][4][5] It was found that these catalytic reactions are much easier to carry out and considerably less expensive.…”
mentioning
confidence: 99%
“…[3] To solve this problem, several research groups have developed copper-catalyzed alkylation reactions of Grignard reagents. [3][4][5] It was found that these catalytic reactions are much easier to carry out and considerably less expensive. Additives, such as 1-methyl-2-pyrrolidinone and 1-phenylpropyne, were originally used to promote the alkylation reactions, [4] and the slow addition of the Grignard reagent was found to provide similar results in a recent study.…”
mentioning
confidence: 99%
See 3 more Smart Citations